2020
DOI: 10.1007/s42452-020-2256-8
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin: synthesis and characterization of bioflavonoid complex

Abstract: Flavonoids are widely recognized for their beneficial effects in the cosmetic industry, possessing many biological activities, such as antioxidant, anti-inflammatory and antimicrobial properties. The study presented an efficient and simple solution to improve the preparations of antioxidant complexes based on hesperidin. Obtained products are characterized by thermogravimetric, spectrophotometric method, electron scanning microscopy, color analysis and zeta potential. Lightness value (L*) of hesperidin-silica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 29 publications
(32 reference statements)
3
14
0
Order By: Relevance
“…It was also reported that hesperidin glycosylated form and hesperidin complex has high thermal stability, but pure hesperidin has low thermal stability. These structural differences cannot be detected with the HPLC technique [ 38 ], but they can be distinguished with LC-MS/MS. In this study, we used LC-MS/MS to specifically determine only limonin and hesperidin.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that hesperidin glycosylated form and hesperidin complex has high thermal stability, but pure hesperidin has low thermal stability. These structural differences cannot be detected with the HPLC technique [ 38 ], but they can be distinguished with LC-MS/MS. In this study, we used LC-MS/MS to specifically determine only limonin and hesperidin.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular protective effects of hesperidin are expressed in decreasing diastolic blood pressure, glucose levels and various lipid profile parameters, reducing platelet aggregation and increasing in the expression of antioxidative enzymes [74][75][76][77]. Some literature stated that hesperidin also exhibits cardioprotective effect against doxorubicin cardiotoxicity, which is widely used anticancer drug [14,74].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Hesperidin is a flavanone glycoside found in citrus isolated in 1828 by French chemist Lebreton from the white inner layer of citrus peels (mesocarp, albedo) [ 28 ]. The structure consists of a flavanone aglycone, hesperetin, similar to naringenin, which differs from it for the different pattern of substitution on the B ring, which is functionalized with hydroxy group on 3′ carbon and methoxy group on 4′ carbon, whereas the naringenin lacks the methoxy group ( Figure 13 ) [ 29 ].…”
Section: Chemistrymentioning
confidence: 99%